La participación del Prosumidor en la nueva era de la comunicación - Jordán Correa, Dennys (2017)
Technology promotes that communities are more interactive and the prosumer is the protagonist. They generate information as part of the new wave of knowledge; in some cases, changing stereotypes and exerting influence in the way of elaborating and consuming contents. Hence the need to focus on an education that is able to train these generators of information to produce suitable texts. In today's society, prosumers represent the largest digital current since the industrial revolution; at this time, the message can be individual; and, above all, segmented.